The correct statement is that the value of x for System A will be equal to the value of y for System B because the first equation of System B is obtained by adding −4 to the first equation of System A and the second equations are identical. Option D
6x + y = 2 2x − 3y = −10 System A
-x − y = −3 −x − y = −3 System B
Let;s solve for x and y in system A
6x + y = 2
Make 'y' the subject
y = 2-6x
Substitute in the other equation
-x -y = -3
-x - (2-6x) = -3
-x -2+6x = -3
Collect like terms
5x = -3+2
x = -1/5
Substitute in y = 2-6x to find 'y'
y = 2- 6(-1/5)
y = 2+ 6/5
y = [tex]\frac{10+ 6}{5}[/tex]
y = 16/5
For system B
-x-y = -3
Make y subject, we have
-x + 3 = y
y = -x + 3
Substitute in the other equation, we have
2x − 3y = −10
2x - 3(-x+3) = -10
2x + 3x -9 = -10
Collect like terms
5x -9 = -10
5x = -10 + 9
x = 1/5
Substitute into y = -x + 3 to find 'y'
y = -(1) + 3
y = 2
Thus, the correct statement is that the value of x for System A will be equal to the value of y for System B because the first equation of System B is obtained by adding −4 to the first equation of System A and the second equations are identical. Option D
Learn more about simultaneous equations here:
https://brainly.com/question/16863577
#SPJ1